Novel chitosan and bacterial cellulose biocomposites tailored with polymeric nanoparticles for modern wound dressing development - Paul-Octavian Stanescu; Ionut-Cristian Radu; Rebeca Leu Alexa; Ariana Hudita; Eugenia Tanasa; Jana Ghitman; Oana Stoian; Aristidis Tsatsakis; Octav Ginghina; Catalin Zaharia; Mikhail Shtilman; Yaroslav Mezhuev; et al. (Taylor & Francis Group, 2021)
Dressing biomaterials play a key role in wound management keeping a moisture medium and protecting against external factors. Natural and synthetic materials could be used as dressings where chitosan and bacterial cellulose is one of the most important solutions. These biopolymers have been used for wound dressing based on their non-toxic, biodegradable, and biocompatible features. In this study, biocomposites based on bacterial cellulose and chitosan membranes tailored with antimicrobial loaded poly(N-isopropylacrylamide)/polyvinyl alcohol nanoparticles were prepared. Core-shell polymeric nanoparticles, bacterial cellulose/chitosan membranes, and biocomposites were independently loaded with silver sulfadiazine, a well-known sulfonamide antibacterial agent used in the therapy of mild-to-moderate infections for sensitive organisms. The chemistry, structure, morphology, and size distribution were investigated by Fourier transformed infrared spectroscopy (FTIR-ATR), RAMAN spectroscopy, Scanning electron (SEM) and Transmission electron microscopy (TEM), and Dynamic light scattering (DLS). In vitro release behaviors of silver sulfadiazine from polymeric nanoparticles and biocomposites were investigated. The biological investigations revealed good biocompatibility of both the nanoparticles and the biocomposites in terms of human dermal fibroblasts viability and proliferation potential. Finally, the drug-loaded polymeric biomaterials showed promising characteristics, proving their high potential as an alternative support to develop a biocompatible and antibacterial wound dressing.